Adult Human Neurogenesis: From Microscopy to Magnetic Resonance Imaging - Sierra, Amanda; Encinas, Juan M.; Maletic-Savatic, Mirjana (Frontiers in Neuroscience, 2011)
Neural stem cells reside in well-defined areas of the adult human brain and are capable of gene-rating new neurons throughout the life span. In rodents, it is well established that the new born neurons are involved in olfaction as well as in certain forms of memory and learning. In humans, the functional relevance of adult human neurogenesis is being investigated, in particular its implication in the etiopathology of a variety of brain disorders. Adult neurogenesis in the human brain was discovered by utilizing methodologies directly imported from the rodent research, such as immunohistological detection of proliferation and cell-type specific biomarkers in postmortem or biopsy tissue. However, in the vast majority of cases, these methods do not support longitudinal studies; thus, the capacity of the putative stem cells to form new neurons under different disease conditions cannot be tested. More recently, new technologies have been specifically developed for the detection and quantification of neural stem cells in the living human brain. These technologies rely on the use of magnetic resonance imaging, available in hospitals worldwide. Although they require further validation in rodents and primates, these new methods hold the potential to test the contribution of adult human neurogenesis to brain function in both health and disease. This review reports on the current knowledge on adult human neurogenesis. We first review the different methods available to assess human neurogenesis, both ex vivo and in vivo and then appraise the changes of adult neurogenesis in human diseases.